The Potential of Artificial Intelligence in Utilizing Circular Business Models : A Systematic Literature Review - Panu, Julia (My University, 2021)
Artificial intelligence is one of the fourth industrial revolution technologies that have been utilized in organizations. This research studies the potential benefits that artificial intelligence can provide to the organization in combination to circular economy. A concept of “sustainable industry 4.0” is introduced as the one concept that describes the sustainable dimension of industry 4.0 and combines circular economy and the technologies of industry 4.0. Focusing on the artificial intelligence benefits, especially in circular business models, provides the viewpoint of sustainability to artificial intelligence. Challenges and barriers to sustainable industry 4.0 and specially to utilizing artificial intelligence through circular economy and circular business models are presented. The research focuses on business-driven transition to circular business models from the linear model with the support of artificial intelligence. The aim of this research is to identify the potential of artificial intelligence and whether it provides the organization a competitive advantage. At the same time, providing knowledge of sustainable industry 4.0 and circular business models to ease the transition towards circularity for organizations. The research question of potential benefits provided by artificial intelligence technologies to the organization when transitioned to circular business models is answered by conducting a systematic literature review. From a total of 1634 articles, 11 papers were selected as primary study. The systematic literature review resulted in finding multiple benefits provided by artificial intelligence to organization while enhancing the transition to circular business models. Generally, the results provided a confirmation on how artificial intelligence can accelerate the transition to circularity through sustainable development goals and reciprocally sustainability provides a multifaceted platform for the artificial intelligence to work. Results presented how for example, artificial intelligence and machine learning algorithms supported decision making is the most prominent artificial technology for the organization to be beneficial. Besides the enhanced decision making, the results presented as benefits the flexibility of AI, which helps the organization to adapt to changes in the digital age as also the AI supported foundation for strategic development that leads to more sustainable business models. The results also presented drivers for organization to utilize artificial intelligence through circular business models. Such as savings and cost reductions, increased transparency and trust from consumers, and sustainable competitive advantage is seen as drivers for the organization to utilize artificial intelligence to achieve sustainable development goals.

Tekoäly on yksi neljännen teollisen vallankumouksen teknologioista, joita on hyödynnetty organisaatioissa. Tämä tutkimus tutkii mahdollisia hyötyjä, joita tekoäly yhdistettynä kiertotalouteen voi tarjota organisaatiolle. Tutkimus esittele käsitteen "kestävä teollisuus 4.0", joka kuvaa teollisuus 4.0:n kestävää ulottuvuutta sekä yhdistää kiertotalouden ja teollisuus 4.0:n teknologiat. Keskittymällä erityisesti tekoälyn tuomiin etuihin kiertotalouden liiketoimintamalleissa, tutkimus tarjoaa kestävän näkökulman tekoälylle. Kestävän teollisuus 4.0:n ja erityisesti tekoälyn hyödyntämisen haasteita ja esteitä esitellään kiertotalouden ja kiertotalouden liiketoimintamallien kautta. Tutkimus keskittyy liiketoimintalähtöiseen siirtymiseen kiertotalouden liiketoimintamalleihin nykyisestä lineaarisesta talousmallista tekoälyn tuella. Tämän tutkimuksen tavoitteena on tunnistaa tekoälyn potentiaali ja todentaa tarjoaako se organisaatiolle kilpailuetua. Samalla tarjotaan tietoa kestävästä teollisuus 4.0:sta ja kiertotalouden liiketoimintamalleista helpottamaan organisaatioiden siirtymistä kiertotalouteen. Tutkimuskysymyksenä on: millaisia mahdollisia hyötyjä tekoäly voi antaa yritykselle siirryttäessä kiertotalouden liiketoimintamalleihin. Tutkimuskysymykseen vastataan systemaattisen kirjallisuuskatsauksen avulla. Yhteensä 1634 artikkelista valittiin 11 artikkelia ensisijaiseksi materiaaliksi (primary study). Systemaattisen kirjallisuuskatsauksen tuloksena löydettiin useita tekoälyn tarjoamia etuja organisaatiolle siirryttäessä kiertotalouden liiketoimintamalleihin. Yleisesti ottaen tulokset vahvistivat, kuinka tekoäly voi nopeuttaa siirtymistä kiertotalouteen kestävän kehityksen tavoitteiden kautta ja miten vastavuoroisesti kestävyys tarjoaa monipuolisen alustan tekoälylle toimia. Tulokset esittivät, kuinka esimerkiksi tekoälyn ja koneoppimisalgoritmien tukema päätöksenteko on merkittävin keinotekoinen teknologia organisaation hyödyksi. Tehostetun päätöksenteon lisäksi tulokset esittivät hyötyjä olevan muun muassa tekoälyn joustavuus, joka auttaa yritystä toimimaan digitaalisella aikakaudella muutoksiin sopeutuen sekä tekoälyn tukema perusta yrityksen strategiselle kehittämiselle kohti kestävämpiä liiketoimintamalleja. Tulokset esittelivät myös kannustimia organisaatiolle tekoälyn hyödyntämiseen kiertotalouden liiketoimintamallien kautta. Esimerkiksi säästöt ja kustannusten väheneminen, lisääntynyt läpinäkyvyys ja kuluttajien luottamus sekä kestävä kilpailuetu nähdään kannustimina organisaatiolle tekoälyn hyödyntämiseen kestävän kehityksen tavoitteiden saavuttamiseksi.
Keywords: business models; circular economy; sustainable development; decision making; artificial intelligence; fi=Tietojärjestelmätiede|en=Information Systems|; fi=Teknisen viestinnän maisteriohjelma|en=Master's Programme in Technical Communication|sv=Magisterprogrammet i teknisk kommunikation|